Consumption pattern and demand analysis of dacryodes edulis in Umuahia metropolis of Abia State (2015)
Consumption pattern and demand analysis of Dacryodes edulis commonly called ube by the Igbos in Umuahia, Nigeria was studied. The various uses and reasons for consumption of Dacryodes edulis, socio- economic characteristics of respondents, income elasticity, regression of the significance of socio-economic variables on demand for Dacryodes edulis, correlation of socio-economic status and consumption are addressed. Simple random sampling was adopted. A well structured questionnaire were used for Dacryodes edulis consumers at the household in two selected local government areas in Umuahia. A total of (160) one hundred and sixty questionnaires were administered, on a total of eight (8) villages. Data obtained were subjected to simple descriptive statistics, which shows that almost all the respondents (92.0%) consume Dacryodes edulis and they got to know of Dacryodes edulis through family and friends due to its high medicinal value as claimed by 91.3% of the respondents. Results indicated a significant descriptive (p<0.05) contribution of the inde~ndent variables on the quantity of Dacryodes edulis consumed. The coefficient of determination (R) which is 58% makes the model fitted well to the data. The marital status has the highest contribution (0.179) to the quantity of Dacryodes edulis consumed, this is followed by willingness to buy (0.167), how often (0.137), household size (0.116), age (0.1(0) educational level (0.099), price of purchase (0.095) and profession (0.068).The income elasticity of Dacryodes edulis demand is 13%. The income elasticity is significant at 5% with coefficient of 0.13, this means that a percent increase in income leads to a 13%, of change in Dacryodes edulis consumption. The correlation shows that the quantity purchased and how often you buy Dacryodes edulis is significant (-0.5807) and also the quantity purchased and price quantity of purchase each time is also significant (0.6440).